Influence of welding parameters on mechanical property during friction stir welded joint on aluminium alloys: a review - Aditya Mamgain; Vivek Singh; Ajay Pratap Singh (Penerbit Universiti Kebangsaan Malaysia, 2023)
The friction stir welding (FSW) is widely used in the fabrication of Aluminium alloy and other non-ferrous alloy. It has good potential to be used in major industries such as automobiles, aerospace, shipbuilding and can be used in the joining of high strength alloys. The FSW process low distortion and heat affected zone (HAZ) with fine recrystallized microstructure which leads to better mechanical properties at the weld zone and produces great stability. In this study, the different FSW parameters such as weld speed, tool rotation speed, tool tilt angle, feed per min has been discussed. The different types of tool pin profile and shoulder have also been discussed and their impacts on mechanical and microstructural properties at welded joints. Among various welding parameters the rotational speed is the most influencing parameter in FSW. Increasing the rotational speed exhibits the increase at tensile strength and is supposed to improve the mechanical properties. The most affected tool pin profile would be considered to be tapered threaded cylindrical pin profile which makes the adequate mixing of material with better flow ability and provide the fine grains at nugget zone. Comparing the FSW with other arc welding processes, it shows a wide range of environmental benefits which are noticeable such as saving in consumable materials, decrease in consumption of filler material and reduction in grinding wastes. Harmful emissions created from arc welding causes a health hazard to the welder. For achieving the high joint-strength for aerospace aluminium alloys and high temperature sustainable metallic alloys, friction stir welding will be preferred.